(untitled) (Jurnal Simki Economic, 2025)
This study aims to examine the implementation of Village Fund allocations directed at supporting the food security program in Lempangang Village, from 2022 to 2025. This study also discusses the extent to which the program contributes to community welfare and its relationship to climate change issues. The study used a qualitative descriptive approach, with data collection techniques including in-depth interviews and questionnaires distributed to village government officials, program implementers, and beneficiaries in the community. The findings indicate that the allocation of Village Funds for food security has consistently met the minimum requirement of 20% annually. The implemented programs include seed procurement, irrigation system construction, fish farming in ponds, nutrition garden management, and chicken farming. These initiatives have had a positive impact in terms of increasing local food availability, meeting the nutritional needs of vulnerable groups (such as pregnant women and children at risk of stunting), and efficient use of village funds. Furthermore, this local potential-based food security approach is considered to have the potential to contribute to climate change mitigation efforts, including through more local and sustainable food consumption patterns. The research recommends the need for more flexible program planning, involving active community participation, and integrating environmental sustainability principles into the future management of the Food Security Fund.